2021
DOI: 10.3390/ijms22094780
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic Receptors and BK Channels Are Affected by Lipid Raft Disruption of Salivary Gland Cells

Abstract: Activity-dependent fluid secretion is the most important physiological function of salivary glands and is regulated via muscarinic receptor signaling. Lipid rafts are important for G-protein coupled receptor (GPCR) signaling and ion channels in plasma membranes. However, it is not well understood whether lipid raft disruption affects all membrane events or only specific functions in muscarinic receptor-mediated water secretion in salivary gland cells. We investigated the effects of lipid raft disruption on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…The specificity of lipid raft targeting was validated by the reduced fluorescent signal observed when cholesterol was depleted in cellular lipid rafts using methyl-β-cyclodextrin (MβCD) (Figure 2). 46 Additionally, we investigated the changes in CTxB-FITC binding after cells were treated with different concentrations of MβCD using CLSM. We found that CTxB-FITC binding to cells decreased with increasing MβCD concentration and reached a plateau at 100 μM (Figure S7).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The specificity of lipid raft targeting was validated by the reduced fluorescent signal observed when cholesterol was depleted in cellular lipid rafts using methyl-β-cyclodextrin (MβCD) (Figure 2). 46 Additionally, we investigated the changes in CTxB-FITC binding after cells were treated with different concentrations of MβCD using CLSM. We found that CTxB-FITC binding to cells decreased with increasing MβCD concentration and reached a plateau at 100 μM (Figure S7).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…There are some limitations to the interpretation of our results. First, in our study, mouse submandibular gland cells were prepared according to previous studies (46)(47)(48). The epithelium, fibroblasts were not able to be separated by this isolation method.…”
Section: Discussionmentioning
confidence: 99%